Oat fiber fractions and their application in breeding programs - Silva, Cláudia Fernanda Lemons e; Milach, Sandra Cristina Kothe; Silva, Sérgio Delmar dos Anjos e; Federizzi, Luis Carlos; Montero, Cândida Raquel; Fontaneli, Roberto Serena (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to determine fiber fraction in oat genotypes and to evaluate the use of NIRS with whole and ground groats. Whole oat groats of UFRGS 7, UFRGS 14 and UFRGS 17 and 99 F7 recombinant inbred lines from UFRGS 7 x UFRGS 17, were analyzed for total fiber, soluble fiber and insoluble fiber contents, by gravimetric-enzymatic method. Samples of whole and ground groats, were also analyzed by NIRS. The results showed that the NIRS method was efficient to determine fiber content using whole grain, and it is possible to use it for selection in oat.